Penguatan Kapasitas Masyarakat Melalui Inovasi Formulasi Kebijakan Perencanaan Pembangunan Partisipasif di Kecamatan Wanasalam Kabupaten Lebak - Ahmad Sururi; Rahmi Mulyasih (Universitas Serang Raya, 2017)
The purpose of this community service activity is to co-ordinate with the community in developing innovative and participatory development planning policy formulation in a sustainable manner to produce the document as reference and recommendation of RPJMD and RKPD. The expected impact factor is to encourage the strengthening of the capacity of villagers both individually and in groups through the active participation of the community by utilizing local potentials and resources so as to generate village development planning cadres and transforming them into development policy actors as the subject of policy formulation. Strengthening Community Capacity-based innovation policy formulation is implemented through the following principles: (i) the community is the main actor of the development planner and is positioned as the decision maker / policy maker; (ii) prioritizing the values of local wisdom included in social capital in accordance with social, cultural and geographic characteristics; (iii) village governments are facilitators who facilitate village communities in developing innovative development planning policy formulations. The method used is Participatory Rapid Appraisal (PRA) or participatory village appraisal. The results of community service activities run in accordance with the predetermined plans. The stages of advisory activities are running well from socialization, observation and survey, identification, problem solving analysis and preparation of development planning documents to be handed over to village government as recommendation / reference materials for the preparation of RPJMD and RKPD.